Physical-chemical and technological characterization of dryed biofortified sweet potato flour in different temperatures (Research, Society and Development, 2020)
The sweet potato (Ipomoea potatoes (L.) Lam.) Of the orange pulp stands out for being an abundant source of β-carotene, but one of the biggest challenges is its high water content that makes the durability of its useful life be reduced. One of the alternatives to extend the shelf life is drying, the processing of this tuber can contribute to the valorization of the culture and the development of new products. The objective was to characterize the biofortified sweet potato pulp flour dried at different temperatures. The biofortified sweet potatoes (access CNPH1210) were dried in an oven with forced air ventilation, in four temperature conditions: 45, 55, 65 and 75 ° C. Drying continued until the sliced ​​roots reached a water content of 14% (b.u.). Proximal composition, pH, acidity, water absorption index, oil absorption index and milk absorption index were evaluated. Flours obtained from sliced ​​roots dried at 45, 55, 65 and 75ºC were stable in their proximal composition. The flour has favorable technological characteristics, it can be used as a topping for breaded or for crunchy products.